(untitled) (KULT_online, 2024)
Barbara Tepa Lupack’s The Othering of Women in Silent Film: Cultural, Historical, and Literary Contexts is a comprehensive examination of racial, ethnic, and gender stereotypes in early cinema, with a focus on the representation of women. Lupack examines recurring tropes that are prevalent in silent film and sheds light on the broader social and cultural contexts that influenced these representations. The book is organized into eight chapters, each devoted to a specific underrepresented or misrepresented group in silent film.